Harnessing Serbian Civilian Capacity for Peace Support Operations: A Nascent Community? - Savković, Marko; Karlsrud, John (Journal of Regional Security, 2018)
The article will explore the possible emergence of a civilian capacity community in Serbia comprised of Serbian policymakers, researchers and practitioners who are interested in peace support operations and willing to deploy Serbian experts through multilateral organizations such as the European Union, United Nations and the Organization of Security and Co-operation in Europe. Having recently undergone a security sector reform, Serbia can offer to share relevant experience and expertise with these organizations through secondment or direct hire, in order to support the countries experiencing complex crises or those that are emerging from conflict. Serbian expertise can serve to soften some of the criticism leveled against peace support operations and provide relevant expertise to those in the field.